Fast Hilbert Transform - Suprajitno Munadi (Scientific Contributions Oil and Gas, 1988)
The use of Hilbert Transform is becoming more and more Important for analysis and processing of geophysical data. However, the direct mathematical formulation in the form of contour integration is not easy to pro. A specific formulation which relates the Hilbert transform and the Fourier transform has been established for developing a computer Programme. This relationship enables us to execute the Hilbert Transformation in a very quick manner using the well known Fast Fourier transform algorithm.The application of this method for generating quadrature seismic trace and recovering minimum phase specimum from the magnitude demonstrates the effectiveness of the programme. The conversion of non-minimum phase seismic wavelet whichas similar spectral magnitude can be done using the hilbert transform.